2016
DOI: 10.1186/s40317-016-0106-7
|View full text |Cite
|
Sign up to set email alerts
|

Contrasts in the movements and habitat use of juvenile and adult white sharks (Carcharodon carcharias) at Guadalupe Island, Mexico

Abstract: Background: Although the effort in the study of white sharks in Mexico is rapidly elucidating adult biology, almost nothing is known about the juveniles. Current understanding of this life history is based largely on the incidental take of juveniles in nursery grounds in the Pacific coast of Baja California and some individuals tagged in the USA that have migrated to Mexican waters. Also, it is not known how or when they recruit to adult aggregation sites or how they learn to make seasonal migrations offshore.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
62
1

Year Published

2019
2019
2021
2021

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 51 publications
(71 citation statements)
references
References 25 publications
2
62
1
Order By: Relevance
“…Guadalupe Island Biosphere Reserve (29°00′N, 118°26′W) is located 240 km off Baja California's coast, Mexico (Gallo‐Reynoso & Figueroa‐Carranza, ). This oceanic environment is characterized by the abundance of macroalgae, invertebrates, bony fishes, elasmobranchs, cetaceans, and pinnipeds, such as the California sea lion Zalophus californianus , the northern elephant seal Mirounga angustirostris , and the Guadalupe fur seal Arctocephalus townsendi (Gallo‐Reynoso & Figueroa‐Carranza, ; Hoyos‐Padilla et al, ). Abundance of prey has been suggested as one of the main reasons for the seasonal presence of white sharks in this aggregation site during July to January of each year (Domeier & Nasby‐Lucas, ; Hoyos‐Padilla et al, ; Jaime‐Rivera et al, ).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Guadalupe Island Biosphere Reserve (29°00′N, 118°26′W) is located 240 km off Baja California's coast, Mexico (Gallo‐Reynoso & Figueroa‐Carranza, ). This oceanic environment is characterized by the abundance of macroalgae, invertebrates, bony fishes, elasmobranchs, cetaceans, and pinnipeds, such as the California sea lion Zalophus californianus , the northern elephant seal Mirounga angustirostris , and the Guadalupe fur seal Arctocephalus townsendi (Gallo‐Reynoso & Figueroa‐Carranza, ; Hoyos‐Padilla et al, ). Abundance of prey has been suggested as one of the main reasons for the seasonal presence of white sharks in this aggregation site during July to January of each year (Domeier & Nasby‐Lucas, ; Hoyos‐Padilla et al, ; Jaime‐Rivera et al, ).…”
Section: Methodsmentioning
confidence: 99%
“…Knowledge about C. carcharias around Guadalupe Island is derived from a limited number of studies related to migration (Domeier & Nasby‐Lucas, ), ecology (Becerril‐García, ; Bonfil & O'Brien, ; Hoyos‐Padilla, Klimley, Galván‐Magaña, & Antoniou, ; Jaime‐Rivera, Caraveo‐Patiño, Hoyos‐Padilla, & Galván‐Magaña, ), and local movements (Hoyos‐Padilla et al, ; Skomal, Hoyos‐Padilla, Kukulya, & Stokey, ). There is no ethological research describing the surface behaviour of white sharks related to cage‐diving boats in Mexico or in the whole eastern Pacific, despite its importance for the Mexican authorities (Becerril‐García, ; Torres‐Aguilar et al, ).…”
Section: Introductionmentioning
confidence: 99%
“…For instance, Hoyos‐Padilla et al . () found that adult white sharks ( Carcharodon carcharias ) utilized broader home ranges than juveniles. Other examples are available in sea birds, such as Cory's shearwater ( Calonectris diomedia ), in which immature individuals and adults use different migration routes (Péron & Grémillet, ).…”
Section: Introductionmentioning
confidence: 99%
“…Other examples are available in sea birds, such as Cory's shearwater ( Calonectris diomedia ), in which immature individuals and adults use different migration routes (Péron & Grémillet, ). However, the effects of age may mask the effects of maturity in studies comparing immature and mature individuals by separating individuals based on their age (Hoyos‐Padilla et al ., ; Péron & Grémillet, ). A similar issue arises when all individuals belonging to the same cohort mature at once as age effects mix with maturity effects (Lucifora et al ., ).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation